2013 IEEE 63rd Electronic Components and Technology Conference 2013
DOI: 10.1109/ectc.2013.6575765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature gradient on moisture diffusion in high power devices and the applications in LED packages

Abstract: High power electronic devices create hot spots, which give rise to the junction temperature significantly higher than the ambient temperature. This induces a situation that the moisture diffusion from environment to device is in the direction against temperature gradient direction. In addition, far field relative humidity is different from the environment surrounding the packaged devices. In this paper, two mechanisms of moisture transport are studied. First, the localized relative humidity related to the far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…14. Same observation had also been observed by Fan et al [32]. The effect of moisture ingress into the electronic packages, though not LED packages, had been reported as considerable even at a low relative humidity of 10%, as in the case of the aging chamber [33].…”
Section: Package Degradation Investigation By Physics Analysissupporting
confidence: 55%
“…14. Same observation had also been observed by Fan et al [32]. The effect of moisture ingress into the electronic packages, though not LED packages, had been reported as considerable even at a low relative humidity of 10%, as in the case of the aging chamber [33].…”
Section: Package Degradation Investigation By Physics Analysissupporting
confidence: 55%
“…Heat generated inside LEDs must be effectively released out of the system to the environment; otherwise the LED's operating temperature will become higher and higher. Many studies have shown that high operating temperature can damage the LED package in several ways, such as lumen depreciation, die-attach delamination, epoxy degradation, high mechanical stresses due to mismatch of thermal expansion coefficients of materials, decrease of electron-hole recombination efficiency in the active layer, and color shift [5,6,[10][11][12]. Any of these effects can reduce the useful LED lifetime significantly.…”
Section: Introductionmentioning
confidence: 99%